Fracture toughness and failure mechanism of high performance concrete incorporating carbon nanotubes - Anwar Khitab; Sajjad Ahmad; Rao Arsalan Khushnood; Syed Ali Rizwan; Giuseppe Andrea Ferro; Luciana Restuccia; Mustajab Ali; Imran Mehmood (Fracture and Structural Integrity)
Cement and concrete composites are inherently brittle and exhibit very less tensile/flexural strength capacity as compared to their compressive strength. Use of thoroughly dispersed carbon nanotubes in the concrete matrix is one of the possible solution for enhancing mechanical properties in tension/flexure. In the present research work, small fractions of multiwall carbon nanotube (MWCNTs) i.e. 0.05 and 0.10 wt% of cement have been integrated into the cement concrete to study their effect on the mechanical properties of the resultant concrete mixtures. The enhanced performance of the whole mix lies on a single point that MWCNTs must be thoroughly disperse in the mixture. Hence, special arrangement through usage of high energy sonication along with amended acrylic based polymer (performing as a surfactant) was made to have a uniform dispersion of MWCNTs in the concrete mix. The testing of concrete samples includes i.e., flexure, splitting tensile and compressive strengths after 3, 7, 28 and 56 days of curing. After having comparison with the control mix cured for 28 days, it was observed that the addition of 0.05 wt% MWCNTs increased the splitting tensile strength by 20.58%, flexural strength by 26.29% and compressive strength by 15.60%. Through above results, which verify the increase in concrete mix strength after adding MWCNTs, these MWCNTs may be incorporated in the treatment of Nano/micro cracks completed through process of connecting, branching and pinning. Similarly, as proved in threepoint bending tests, MWCNTs also enhances the breaking strains as well as the fracture energy of the concrete mixes, besides, imparting increase to the strength. The investigations have shown that incorporating lesser amounts of MWCNTs i.e., 0.05 and 0.10 wt% of cement to the concrete mixes after insuring there complete dispersion, unusually improve their properties like mechanical strengths and fracture behavior.